Textual review as a form of reflective evaluation and interactive construction between teacher and student (Olhar de Professor, 2022)
The present work deals with the problem of textual evaluation from the perspective textual-interactive (RUIZ, 2001). After theoretical studies on the subject (FUZER, 2012; FUZER; WEBER, 2012; MENEGASSI, GASPAROTTO, 2013, 2016), the objective is to explain the importance and meaning of methodological strategies, such as guidance notes, notes, questions and comments, have in improving written production, since they represent a dialogical tool used between teacher and student in order to review and qualify the text. Through examples that are based on this perspective of evaluation, the relevance of the textual review is evidenced from this interactive bias. As a result of the research, because they are based on an interactive conception of language and on a procedural understanding of the text, they allow the student to get in touch with their production in a different way from the traditional correction, which makes them differentiated teaching methodologies.
Keywords: Interaction. Text production. Perspective of textual-interactive correction. Textual revision.